Development of Fulminant Type 1 Diabetes Mellitus in a Patient with DRESS Syndrome - Pedro Perez; Wilson Sze; Daniel Lozeau; Dipa Avichal; Joshua Miller (Case Reports in Endocrinology)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome, also known as drug-induced hypersensitivity syndrome, is a serious, sometimes lethal, immunological reaction to drug metabolites involving multiple organ systems. Some of the common causative agents of DRESS include allopurinol, minocycline, sulfasalazine, azathioprine, antiepileptic drugs, and hydroxychloroquine. DRESS is often misdiagnosed and challenging to clinically manage due to the disease’s myriad presentations, acute complications, and long-term sequela after initial resolution. We present the case of a 39-year-old female patient that developed type 1 diabetes as a sequela of DRESS. The patient originally presented to the emergency department with three days of fevers and a pruritic erythematous maculopapular rash that began two weeks prior. She had recently started an antibiotic course and had also been on a long-term antiepileptic drug regimen. Following a thorough clinical examination, the patient was diagnosed with DRESS and treated accordingly. Over the next four months, she went on to have multiple hospitalizations with several admissions to the medical intensive care unit. She had numerous complications including significant facial edema, seizures, bacterial pneumonia, sepsis, hypovolemic shock, acute respiratory distress syndrome, diabetic ketoacidosis, nonalcoholic steatohepatitis, liver failure, and recurring DRESS rashes despite treatment with high-dose intravenous steroids and immunosuppressants. During this time, the patient developed a rare form of uncontrolled type 1 diabetes mellitus not explained by autoantibody production or continued high-dose steroid use. Fulminant type 1 diabetes mellitus is a sequela of DRESS that is poorly understood and rarely reported. When it occurs, it significantly and negatively affects patient prognosis and requires careful monitoring to assure proper glycemic control.